MATRIX INDEX OF INCOME VARIETIES OF INDONESIAN LABOR FORCE AND ITS APPLICATION IN INDONESA - Syarwani Canon (Faculty of Economics and Business, Universitas Gadjah Mada, 2012)
Matrix Index of Income Varieties (MIVP) is an index, which is developed from the variety co efficiency and statistic χ2 so that it will produce output totally as shown by Index of Williamson/Theil, as regionally as Index of Theil, sectorally as Index of Gini.Besides, Matrix Index of Income Varieties (MIIV) is able to identify which individual/ sector/region influence the draw of income inequalities above or below the average. In application, MIIV will produce a maximal outcome if it is combined with Labor Force Productivity Index.The outcome of MIIV/MIVP in Indonesia shows that the high-income inequalities in Indonesia are influenced by the contribution of regional economy, regional labor force contribution, the characteristic of regional economic sector, and regional potentials of each province.Keywords: income distribution, total, region, sector, regional sector